Design of ultrasonic transducer for leakage detection on PVC water pipeline - Chamran, Mohammad Kazem (2014)
Nowadays most of the water pipelines for domestic and commercial areas are made from polyvinyl chloride (PVC). It has advantages such as lighter weight, higher flexibility to comply with ground quake and tremble, higher resistibility to corrosion as a result of climate and temperature changing, along with lower production and installation cost. However, it has less resistibility to endure pressures either from inside or outside the pipeline. Since these pipelines are not for valuable liquids such as petroleum, there is no particular monitoring system available for them yet. In many cases, leakage occurs for months or even years and they cannot be detected unless the leakage effect becomes significant. According to a study 10% of US water pipelines had water loss which estimated to cost around $4.3 billion per year. Almost the same percent of loss or even more is existing in European counties. Therefore having a simple and affordable monitoring system is necessary for natural resources conservation. The conventional pipelines monitoring systems are commonly used to monitor long distance metallic petroleum pipelines and they are not reliable for monitoring the short distance PVC pipelines. This thesis discussed a non-invasive ultrasonic PVC pipelines monitoring system with modified V-topology. The proposed technique uses a pair of 40 KHz ultrasonic transducers with designed interface circuitries for emitting and receiving the signal. The designed interface circuits improved the emitted and received signal along with reduces of power consumption. The analysis carried includes signal fitness recognition and normalized cross-correlation that compared the transmitted and received signal. The developed system consumed 2.5W which can be supply from USB port. The proposed technique is for leak detection with power consumption around 2.5 watts, which can be supplied from universal serial bus or any available battery with more than 0.5 mA current injection. In wireless communication system is transmitting results of pipe monitoring in conjunction with temperature and humidity to the center. This information is available in installed on board LCD and designed webpage through online access. In comparison with available techniques, this ultrasonic monitoring is non-invasive to pipeline as there is no contact or involvement with it. Proposed method is designed to monitor physical condition of PVC pipelines and differentiate pipe with leakage from a healthy pipeline by use of air-coupled transducers. The system’s operation has been tested on a general size PVC pipeline with 60 mm diameter for different size of orifices from 3 mm to 6 mm. As a result of experimental tests, system was able to detect orifices as small as 4.5 mm and greater accurately. System applied on pipeline with and without water and results proved that the pipe with very low pressure has very close trend to pipe without water. Occurrence of leakage in pipeline decreases the strength of received signal and increase of orifice tends to weakening it further. Operation tested for different location angles from 20 to 70 degrees and 60 degree was chosen as relatively high signal strength with recognition accuracy of 94.924% and covering area on pipeline near to 90 cm. Along with leak recognition, this research revealed that the smaller angle contributes to longer transducers distance and less accuracy. Then by increase of central frequency angles, accuracy of recognition reduced as well.